ANALISIS KEBIJAKAN KELAUTAN MENDUKUNG PERCEPATAN PEMBANGUNAN WILAYAH PERBATASAN LAUT NASIONAL DI KABUPATEN BERAU - Dayang Diah Fidhiani; Gusti Haqiqiansyah; Qoriah Saleha; Heru Susilo; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2014)
The aims of the research were to identify livelihood assets fisher, aquaculture and major social actors in the territory of the study, the research was to understand the livelihood strategies of fisher and pond farmer in the region context of vulnerability social, economic and ecological, to investigate the diversification efforts of fisher, to investigate the potential of coastal resources, and formulating marine policy in the national border community based sustainable livelihoods. The research was conducted by survey method. Data collected in the research is the primary and secondary data. The collected data were analyzed by analysis of livelihoods models, GMP analysis, Analysis of Regional Comparative Advantage and SWOT analysis. The results showed that the livelihood assets in Maratua island is fishing, aquaculture, retailer, and the private sector (trade, dive resort). Livelihood strategies are implemented, there are three main components namely: (a) The strategy of fishing effort and fish and lobster; (b) to diversify the direction of tourism development include the development of home stay for domestic and foreign tourists, the sea and culinary guide development tourism, (c) institutional and marketing strategy includes involvement in the patron-client institutions and trade cooperation with buyers from outside the island and abroad. Based on the results can be formulated some general policy recommendations include the implementation of integrated development programs on the Maratua island relating to integration of the planning area, coastal and small islands good governance, the program covers the social, health, economic, and environmental and local cultural, social and institutional strengthening of indigenous communities in the utilization coastal and marine resources, disadvantage groups, implementation of the program taking into account the implementation of regional autonomy and local resources, and using the instruments of economic valuation of coastal resources and the small islands in the formulation of policy utilization of the island.